2010
DOI: 10.1002/ar.21214
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Concept of Stretch Coupling in Smooth Muscle: A Thesis by Lars Thuneberg on Contractile Activity in Neonatal Interstitial Cells of Cajal

Abstract: The hypothesis was put forward by Thuneberg that rhythmically contracting interstitial cells of Cajal (ICC) were sensing stretch of the musculature and that this information was transmitted to smooth muscle cells via peg and socket contacts. The present study provides the evidence for the contractile nature of ICC as perceived by Thuneberg. The contractile activity is shown by video frame subtraction and by tracking areas of interest in sequential video frames. Thuneberg used neonatal ICC in culture maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…with ICCs (Powley et al, 2008; see also Huizinga et al, 2008), and the present observations now illustrate how numerous such varicosities are (see, for example, Figures 1, 2 and 3). The extensive numbers of contact sites of IMAs with ICCs underscore the possibility that IMAs may carry stretch or length signals that originate or are transduced within the ICC-muscle-fiber apparatus of the gut (Huizinga et al, 2010). Both GI smooth muscle fibers (Won et al, 2005; Kraichely and Farrugia, 2007) and ICCs (Won et al, 2005; Kraichely and Farrugia, 2007) have been shown to transduce stretch or length signals.…”
Section: 1 Discussionmentioning
confidence: 99%
“…with ICCs (Powley et al, 2008; see also Huizinga et al, 2008), and the present observations now illustrate how numerous such varicosities are (see, for example, Figures 1, 2 and 3). The extensive numbers of contact sites of IMAs with ICCs underscore the possibility that IMAs may carry stretch or length signals that originate or are transduced within the ICC-muscle-fiber apparatus of the gut (Huizinga et al, 2010). Both GI smooth muscle fibers (Won et al, 2005; Kraichely and Farrugia, 2007) and ICCs (Won et al, 2005; Kraichely and Farrugia, 2007) have been shown to transduce stretch or length signals.…”
Section: 1 Discussionmentioning
confidence: 99%
“…P and Q are individual pixel intensities from the current and subsequent frames respectively, while μ P and μ Q are mean pixel intensities for the 21 × 21 pixel squares in these frames. A simpler function based on the sum of the absolute difference in pixel intensities has also been used (Huizinga et al, 2010 ) but our experience is that this is not a critical factor.…”
Section: The Development Of Video Spatiotemporal Mapping Techniquesmentioning
confidence: 99%
“…The minimum of this function represents the movement in pixels of a point at the center of the square between the successive frames, and hence the local velocity, as the frames are captured at regular time intervals, typically 15 per second (Jähne, 2004 ). Earlier work simply searched for the pixel displacement with the lowest function value (Lentle et al, 2007 ; Huizinga et al, 2010 ). However, the author and co-workers have refined the technique to determine the minimum value by fitting a 2D cubic spline to the cross-correlation data and calculating the minimum value on the fitted spline so as to give the displacement in real numbers, i.e., fractions of a pixel.…”
Section: The Development Of Video Spatiotemporal Mapping Techniquesmentioning
confidence: 99%
“…Slow waves depolarize the neighboring smooth muscle cells, either through gap junctions or peg-and-socket coupling (Torihashi et al, 2002;Huizinga et al, 2010). Under the right combination of neuro-hormonal conditions, the depolarized smooth muscle cells are able to generate contractions based on a series of intracellular Ca 2+ release mechanisms (Karaki and Weiss, 1984).…”
Section: Electrical Conduction System Of the Stomachmentioning
confidence: 99%